Numerical Simulation and Optimization of Inorganic Lead-Free Cs3Bi2I9-Based Perovskite Photovoltaic Cell: Impact of Various Design Parameters - Arnob Das; Susmita Datta Peu; Md Abdul Mannan Akanda; Mostafa M. Salah; Md. Sejan Hossain; Barun Kumar Das (Energies, 2023)
The lead halide-based perovskite solar cells have attracted much attention in the photovoltaic industry due to their high efficiency, easy manufacturing, lightweight, and low cost. However, these lead halide-based perovskite solar cells are not manufactured commercially due to lead-based toxicity. To investigate lead-free inorganic perovskite solar cells (PSCs), we investigated a novel Cs3Bi2I9-based perovskite configuration in SCAPS-1D software using different hole transport layers (HTLs). At the same time, WS2 is applied as an electron transport layer (ETL). Comparative analysis of the various design configurations reveals that ITO/WS2/Cs3Bi2I9/PEDOT:PSS/Au offers the best performance with 20.12% of power conversion efficiency (PCE). After optimizing the thickness, bandgap, defect density, and carrier density, the efficiency of the configuration is increased from 20.12 to 24.91%. Improvement in other performance parameters such as short circuit current (17.325 mA/cm2), open circuit voltage (1.5683 V), and fill factor (91.66%) are also observed after tuning different attributes. This investigation indicates the potential application of Cs3Bi2I9 as a lead-free and stable perovskite material that can contribute to improving the renewable energy sector.